A Study On The Quality Of Lesson Plans On Genre Developed BySMA Muhammadiyah English Teachers Of Surakarta - Prasetyo, Arwin Adin (2012)
This research purposes to describe the quality of lesson plans of genre developed by English teachers in Surakarta. The research type is descriptive evaluative research. The data are lesson plans of genre and the data source of this research is document. The writer employs documentation as the method of collecting data with steps: seeking, collecting data, and giving code. In analyzing the data, the writer identifies three main components of lesson plans such indicators, teaching learning process, and evaluation from English teachers in Surakarta. Based on the PERMEN 41, the percentage of indicator in narrative, hortatory exposition, and spoof are 30, 99%. The percentage shows that the quality of the design of indicators is bad quality based on the theory of Suharsimi. The percentage of teaching learning process in narrative, hortatory exposition, and spoof are 62, 59%. The percentage shows that the quality of teaching learning process is good quality based on the theory of Suharsimi. The percentage of evaluation in narrative, hortatory exposition, and spoof are 24, 77%. The percentage shows that the quality of the design of evaluation is bad quality based on the theory of Suharsimi.